2021
DOI: 10.1186/s13011-021-00399-2
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the effectiveness of dextroamphetamine for the treatment of stimulant use disorder: a qualitative study with patients receiving injectable opioid agonist treatment

Abstract: Background A high proportion of people receiving both oral and injectable opioid agonist treatment report concurrent use of stimulants (i.e. cocaine and or amphetamines), which has been associated with higher rates of continued illicit opioid use and treatment dropout. A recent randomized controlled trial demonstrated the effectiveness of dextroamphetamine (a prescribed stimulant) at reducing craving for and use of cocaine among patients receiving injectable opioid agonist treatment. Following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 34 publications
0
20
0
1
Order By: Relevance
“…1 and Table S3). 17,21,23,24,31,44–116 Finally, 22 RCTs were included (Table S4). 13–16,117–134 Figure 2 illustrates the entire geometric distribution of the treatment arms.…”
Section: Resultsmentioning
confidence: 99%
“…1 and Table S3). 17,21,23,24,31,44–116 Finally, 22 RCTs were included (Table S4). 13–16,117–134 Figure 2 illustrates the entire geometric distribution of the treatment arms.…”
Section: Resultsmentioning
confidence: 99%
“… 26 Similar positive outcomes have been identified in pilot programs in Canada. 27 , 28 Furthermore, a 2021 systematic review 29 found that contingency management was associated with psychostimulant abstinence among people with OUD and STUD when provided alongside OAT.…”
Section: Discussionmentioning
confidence: 99%
“…For example, patients prescribed dextroamphetamine in an OAT clinic in the Netherlands had significant reductions in cocaine use, and significant improvements in physical health, mental health, and social functioning . Similar positive outcomes have been identified in pilot programs in Canada . Furthermore, a 2021 systematic review found that contingency management was associated with psychostimulant abstinence among people with OUD and STUD when provided alongside OAT.…”
Section: Discussionmentioning
confidence: 99%
“…Participants seeking a substitution effect for energy, focus and withdrawal management identify dextroamphetamine as an efficient medication, while participants seeking euphoria from taking stimulants do not find dextroamphetamine effective in offering substitution for illicit stimulants (Palis et al, 2021). Participants also identified integrated services to facilitate medication access as an important factor when considering prescription psychostimulant treatment (Palis et al, 2021). However, barriers to implementation include the lack of access to take-home doses, requiring participants to take the medication at certain time frames that do not always offer relief of withdrawal symptoms or cravings (Palis et al, 2021).…”
Section: Dextroamphetaminementioning
confidence: 99%
“…Participants also identified integrated services to facilitate medication access as an important factor when considering prescription psychostimulant treatment (Palis et al, 2021). However, barriers to implementation include the lack of access to take-home doses, requiring participants to take the medication at certain time frames that do not always offer relief of withdrawal symptoms or cravings (Palis et al, 2021). It should also be noted that this research had a very unique and specific sample of participants who had concurrent opioid and stimulant use disorder diagnoses, and that findings may not be generalizable to people with different demographic profiles receiving treatment in other settings (Palis et al, 2021).…”
Section: Dextroamphetaminementioning
confidence: 99%